Effects of Multistrain Probiotic Supplementation on Sows’ Emotional and Cognitive States and Progeny Welfare - Melody Martins Cavalcante Pereira; Ines Andretta; Carolina Haubert Franceschi; Marcos Kipper; Alexandre Mariani; Thais Stefanello; Camila Carvalho; Júlio Vieira; Luiene Moura Rocha; Andrea Machado Leal Ribeiro (Animals, 2024)
The intensification of production systems has resulted in detrimental effects on sow welfare, which can have an adverse influence on their offspring. Considering the relevance of the microbiota–gut–brain axis, probiotics can mitigate such impacts. To investigate the effects of the dietary inclusion of probiotics on the welfare of sows and piglets, 147 multiparous sows were randomly assigned to two groups: a control group or a group supplemented with a multistrain probiotic from the beginning of pregnancy to the end of lactation. The human–animal relationship (HAR), stereotypic behavior, position changes, salivary cortisol, and plasma serotonin levels were assessed in the sows. The piglets’ back test behavior and organ weight were analyzed. The probiotic-supplemented sows exhibited a better HAR index (p = 0.017), which indicated reduced aversion towards humans. The frequency of stereotypies was not influenced by the treatments. However, the supplemented sows spent more time standing (p = 0.054) and less time lying down (p = 0.008). The cortisol level of the supplemented sows was 50% lower (p = 0.047) and the serotonin levels were 11% higher (p = 0.034) than control animals. The multistrain piglets were more passive and less resistant (p = 0.076) in the back test. The organ weights were not influenced by treatments. In conclusion, the sows supplemented with probiotics showed less fear and more motivation indicators, while their piglets showed less aggression behaviors.